2011
DOI: 10.1103/physrevb.84.054102
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure study of the behavior of mineral barite by x-ray diffraction

Abstract: In this paper, we report the angle-dispersive x-ray diffraction data of barite, BaSO 4 , measured in a diamond-anvil cell up to a pressure of 48 GPa, using three different fluid pressure-transmitting media (methanol-ethanol mixture, silicone oil, and He). Our results show that BaSO 4 exhibits a phase transition at pressures that range from 15 to 27 GPa, depending on the pressure media used. This indicates that nonhydrostatic stresses have a crucial role in the high-pressure behavior of this compound. The new h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 29 publications
12
66
0
Order By: Relevance
“…The orthorhombic structure is a distortion of barite and its appearance as post-monazite phase in CeVO 4 is consistent with the fact that bariterelated structures have been found as HP phases in different monazites [13]. Barite and post-barite structures have been reported for high-pressure phases of CaSO 4 [32], BaSO 4 [31]. In case of anhydrite the barite-related structure has been reported as orthorhombic (Pbnm) phase through a monazite-type phase at high-pressure and high-temperature conditions, while a distorted-barite related phase (P2 1 2 1 2 1 ) is formed at high pressure itself in BaSO 4 [31].…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The orthorhombic structure is a distortion of barite and its appearance as post-monazite phase in CeVO 4 is consistent with the fact that bariterelated structures have been found as HP phases in different monazites [13]. Barite and post-barite structures have been reported for high-pressure phases of CaSO 4 [32], BaSO 4 [31]. In case of anhydrite the barite-related structure has been reported as orthorhombic (Pbnm) phase through a monazite-type phase at high-pressure and high-temperature conditions, while a distorted-barite related phase (P2 1 2 1 2 1 ) is formed at high pressure itself in BaSO 4 [31].…”
Section: Resultssupporting
confidence: 61%
“…After considering several candidate structures, we found that the patterns measured beyond 14.7 GPa can be assigned to an orthorhombic structure with spacegroup symmetry P2 1 2 1 2 1 . In particular, a LeBail analysis allows indexing the pattern measured at 14.7 GPa with a CaSeO 4 -type structure (a = 6.88 Å , b = 5.88 Å, and c = 6.76 Å space group: P2 1 2 1 2 1 , Z = 4) similar to the high-pressure structure recently found in BaSO 4 [31]. The orthorhombic structure is a distortion of barite and its appearance as post-monazite phase in CeVO 4 is consistent with the fact that bariterelated structures have been found as HP phases in different monazites [13].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, compounds adopting this type of structure have been of renewed interest regarding their high-pressure (HP) behaviour 6,[8][9][10][11] . 12 ] dodecahedra) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, much study has gone into MgSO 4 , BaSO 4 , various lithium sulfates, and sulfate salts (Lemos et al 1991;Sakuntala andArora 1999, 2000;Chen et al 2009Chen et al , 2010Brand et al 2010;Machon et al 2010;Crichton et al 2011;Jahn and Schmidt 2010;Zhang and Sekine 2007;Santamaría-Pérez et al 2011;Antao 2012). Hydrated sulfates like gypsum undergo several structural changes below 10 GPa, while others like BaSO 4 exhibit few signs of transformation up to 20 GPa.…”
Section: Introductionmentioning
confidence: 99%